1969
DOI: 10.1037/h0028168
|View full text |Cite
|
Sign up to set email alerts
|

Role of the caudate nucleus in spatial orientation of rats.

Abstract: It was hypothesized that the caudate nucleus functions as part of an egocentric localization system; i.e., a system in which positions in space outside the body are defined by their distance and direction from the observer. Experiment 1 demonstrated that rats suffering damage to the caudate were unable to learn the position of a food reward in a radial maze when this reward was always to be found in a certain constant direction relative to the animal's orientation at its starting point. In Experiment 2 it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
54
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 11 publications
10
54
0
Order By: Relevance
“…The alteration of attention and/or sensory processing, may strengthen response, place, or cue strategies, depending on the surrounding environment. Such an explanation could account for the contradictory results in the literature concerning the role of dorsal striatum in egocentric discriminations (Potegal, 1969;Cook and Kesner, 1988;Kesner et al, 1993;DeCoteau and Kesner, 2000versus Divac et al, 1967, 1978Kirkby, 1969;Pisa and Cyr, 1990;Oliveira et al, 1997).…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The alteration of attention and/or sensory processing, may strengthen response, place, or cue strategies, depending on the surrounding environment. Such an explanation could account for the contradictory results in the literature concerning the role of dorsal striatum in egocentric discriminations (Potegal, 1969;Cook and Kesner, 1988;Kesner et al, 1993;DeCoteau and Kesner, 2000versus Divac et al, 1967, 1978Kirkby, 1969;Pisa and Cyr, 1990;Oliveira et al, 1997).…”
Section: Resultsmentioning
confidence: 55%
“…Several studies have shown impairment in the acquisition of tasks that require the use of an egocentric strategy after lesions of the dorsal striatum (Potegal, 1969;Cook and Kesner, 1988;Kesner et al, 1993;DeCoteau and Kesner, 2000). This position has, however, been challenged by other studies postulating that dorsal striatum is not involved in egocentric discriminations (Divac et al, 1967(Divac et al, , 1978Kirkby, 1969;Pisa and Cyr, 1990;Oliveira et al, 1997).…”
Section: Introductionmentioning
confidence: 73%
“…Although Restle (1957) has made a behavioral analysis of the place vs. response controversy, there have been no studies directly assessing the neural bases of place and response performance. Potegal's (1969) report implies that the brain structures involved in place learning are different from those involved in response learning. He found that caudate nucleus damage prevented rats from learning the position of a food reward in a radial maze when the reward was placed in a constant direction relative to the animal's body position.…”
mentioning
confidence: 89%
“…Finally, and perhaps most importantly, the hypothesis does not take into account the well-established functional heterogeneity of the caudate nucleus, one advantage at least of hypotheses favored by other investigators (Divac, 1968;Potegal, 1969 ;Wmocur,1974).…”
mentioning
confidence: 99%
“…Thus, taken together, the bulk of the evidence suggests that the caudate nucleus is functionally dissociated with respect to AC and that antero-dorsal portions of the structure are not essential for one-way learning. The functional heterogeneity of the rat caudate nucleus has been extended to passive as well as active avoidance learning (Wino cur, 1974), appetitive discrimination tasks (Potegal, 1969), and to a variety of tasks involving other species (see review by Divac, 1968). Kirkby (1973; see also Kirkby & Polgar, 1974) favors a unitary explanation of caudate function.…”
mentioning
confidence: 99%